Trouble (University of Huddersfield Press, 2019)
The latest Grist Anthology is an innovative blend of some of the most exciting and freshest voices in prose today. Protest is the distillation of a simple human experience - to witness a wrong being done, and to do something about it. The stories featured in Trouble celebrate protest, rebellion, disobedience and general bloody-mindedness in all of its forms.